Development of three-dimensional primary human myospheres as culture model of skeletal muscle cells for metabolic studies - Dalmao-Fernandez, Andrea; Aizenshtadt, Aleksandra; Bakke, Hege G.; Krauss, Stefan; Rustan, Arild C.; Thoresen, G. Hege; Kase, Eili Tranheim (Frontiers in Bioengineering and Biotechnology, 2023)
Skeletal muscle is a major contributor to whole-body energy homeostasis and the utilization of fatty acids and glucose. At present, 2D cell models have been the most used cellular models to study skeletal muscle energy metabolism. However, the transferability of the results to in vivo might be limited. This project aimed to develop and characterize a skeletal muscle 3D cell model (myospheres) as an easy and low-cost tool to study molecular mechanisms of energy metabolism. We demonstrated that human primary myoblasts form myospheres without external matrix support and carry structural and molecular characteristics of mature skeletal muscle after 10 days of differentiation. We found significant metabolic differences between the 2D myotubes model and myospheres. In particular, myospheres showed increased lipid oxidative metabolism than the 2D myotubes model, which oxidized relatively more glucose and accumulated more oleic acid. These analyses demonstrate model differences that can have an impact and should be taken into consideration for studying energy metabolism and metabolic disorders in skeletal muscle.